THE EFFECT OF MACERATION METHOD AND SOXHLETATION METHOD ON TOTAL PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY OF KIRINYUH (Chromolaena odorata (L.) R.M.King & H.Rob) LEAF - Renatha Audya Larasati; Nastiti Utami; Novena Yety Lindawati (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
This study evaluated kirinyuh leaf extract as a natural antioxidant using Soxhlet extraction and maceration extraction methods. Dried leaves of kirinyuh were extracted with 96% ethanol. The total phenolic content was measured spectrophotometrically according to the Folin Ciocalteu method, calculated as gallic acid equivalent (GAE), while the antioxidant activity was measured using ABTS. The results of the phytochemical test of kirinyuh leaf extract using maceration (EKM) and Soxhletation (EKS) methods revealed alkaloids, flavonoids, saponins, steroids, and tannins. The total phenolic content of EKM was 39.85 ± 0.20 mgGAE/gram and EKS was 46.95 ± 0.15 mgGAE/gram extract. Antioxidant activity in the form of IC50 EKM was 46.10 ± 0.09 mg/L and EKS was 45.27 ± 0.07 mg/L, both of them have a very strong category. There were significant differences in the total phenolic content and antioxidant activity of the ethanol extract of the Kirinyuh leaf using maceration and soxhletation methods based on the results of the T-test. Keywords: Kirinyuh, Eupatorium odoratum, ABTS, phenolics, antioxidant.